Clays and Clay Minerals, Vol. 59, No. 5, 518–524, 2011. - Ling, Hui; Lu, Anhuai; Wang, Changqiu; Li, Yan; Chen, Peng; Zhou, Jiangong; Wang, Jian (My University, 2011)
Landfill leachate is one of the most difficult effluents with which to deal from an environmental perspective because of its concentration and complex composition, including refractory and toxic components such as heavy metals or xenobiotic organic compounds. The objective of the present study was to use organically modified bentonite (OMB) to dispose of landfill leachate >10 y old. The OMB was synthesized using a new method, which removed four steps (filtering, washing, drying, and grinding) from the traditional process. After treatment using OMB, the chemical oxygen demand concentration (COD concentration, an index of the organic pollutants in the landfill leachate, was determined using the potassium dichromate method) of the landfill leachate sample decreased from 2400 to 245 mg/L in 5 h, i.e. the organic pollutants reduction efficiency was as high as 90%. Gas chromatography-mass spectrometry results indicated that most of the organic compounds were removed during the process. The modified and unmodified bentonite contained in the OMB deal with the hydrophobic and hydrophilic organic pollutants, respectively, resulting in significant degradation of the leachate. The study results have provided a new cost-effective method for treatment of landfill leachate.
Treatment Of Municipal Landfill Leachate With Organically Modified Bentonite
Treatment Of Municipal Landfill Leachate With Organically Modified Bentonite
gsccm59509-lin.pdf-- 209KB
Keywords: Periodicals; Geology; Hydrophilicity; Hydrophobicity; Landfill Leachate; Organic Pollutants; Organically Modified Bentonite (OMB)